Actitudes justificativas del comportamiento agresivo y violento en estudiantes universitarios de la ciudad de Medellin, Colombia 2001 (2002)
ABSTRACT: Attitudes to justify aggressive behavior were studied in a sample of 500 people, 258 females and 242 males, in two public universities of Medellin, Colombia (University of Antioquia and National University) and a private university (Cooperative University of Colombia). The field-work is supported by a theoric frame built on different points of view about aggressiveness, violence and aggression, all of which put in context the results of the study making them meaningful. This work is based on a comparative-descriptive design, and it pretends to compare results by gender and university type. An analysis is carried out about how the studied population uses different types of aggressiveness such as direct, indirect, physical and verbal, in different situations where they find it useful. The indicators used to measure aggressiveness derive from the application of a group of aggression test made from four scales: EXPAGG, DIAS, AQ and EAS; all of the showing a reliable and valid process. The findings show that men use most direct and physical aggression while women are mostly indirect and verbal in their aggressiveness.